The activation and testing of the network CODASYL-DML interface of the M_x001B_p2_x001B_sDBMS using the EWIR database - Werre, Timothy J.; Diehl, Barry A. (Monterey, California. Naval Postgraduate School, 1996)
The Electronic Warfare Integrated Reprogramming Database (EWIRDB) is the primary Department of Defense source for technical parametric performance data on non-communications emitters. A problem of the EWIRDB is that the data are represented in disjoint parametric tree models that are implementation oriented. The parametric tree with its deceptive hierarchical structure, provides a poor modeling construct that obscures the intended semantics and representation of the data, thus making the database difficult to use and understand from a users perspective. The problem addressed by this thesis is to determine if the network model and the network interface of the Multi-Lingual, Multi-Model Database Management System (M2DBMS) in the Laboratory for Database Systems Research at the Naval Postgraduate School is capable of supporting a representative subset of the EWIRDB. The primary goal of this thesis is to implement a representative portion of the EWIR database on the network interface of the M2DBMS. In order to accomplish this goal, the following issues must be addressed: First, the network interface must be activated and returned to its original operational state; second, the network interface must be tested to determine its capabilities and limitations; and lastly, the design and specification of a network EWIR data model must be completed prior to its implementation. We successfully reactivated the network interface to its original operational state. However, testing revealed significant limitations of the network interface. Due to these limitations, only the data definition portion of our proposed design was fully implemented Approved for public release; distribution is unlimited. Lieutenant Commander, United States Navy Captain, United States Army http://archive.org/details/thectivationndte109457849